Polyimide incorporated cyanate ester/epoxy copolymers for high‐temperature molding compounds. Issue 21 (5th October 2018) - Wu, Fan; Song, Bo; Hah, Jinho; Tuan, Chia‐Chi; Moon, Kyoung‐Sik; Wong, Ching‐Ping
ABSTRACT: The rapid development of high‐power devices has driven the requirement for high‐temperature stable epoxy molding compounds. In this work, a designed polymer blend system consisting of cyanate ester/epoxy copolymers modified by polyimide (CE/EP‐PI) has been studied. Polyimide used in this study has shown excellent dispersity in the cyanate ester and epoxy copolymer network (CE/EP), exhibiting homogeneous phase with a denser polymer network structure. With this polymer blend structure, CE/EP‐PI system was proved to have a glass transition temperature as high as 270 °C, increased modulus, and largely enhanced fracture toughness up to 2.06 MPa m 1/2 . CE/EP‐PI resins showed outstanding long‐term stability at high temperature with low mass loss and increased fracture toughness after aging at 200 °C. This work provides a novel insight into the development of molding compounds based on polymer blends system with excellent high‐temperature properties. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 2412–2421 Abstract : The development of high power devices imposes more stringent requirements on the high temperature performance of encapsulation materials. The authors incorporated aromatic polyimide into a cyanate ester/epoxy copolymer system and achieved a polymer blend with an ultrahigh glass transition temperature of 270 °C, largely enhanced modulus and fracture toughness, and improved long term thermal stability. This work provides novel insight into the development of high temperature epoxy molding compounds based on polymer blends.